2017
DOI: 10.5294/aqui.2017.17.3.8
|View full text |Cite
|
Sign up to set email alerts
|

Diagnósticos de enfermagem e modelo adaptativo de roy: análise em pacientes críticos

Abstract: Objetivo: establecer relación de los diagnósticos de enfermería presentes en el dominio seguridad y protección de NANDA Internacional con los problemas adaptativos del modelo de Roy para pacientes en unidad de cuidados intensivos (UCI). Métodos: estudio transversal, llevado a cabo en la UCI de un hospital universitario en una capital del noreste brasileño. La muestra fue de 86 individuos. Los datos, recolectados entre octubre del 2013 y mayo del 2014, mediante formato de entrevista y prueba física, se analizar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
1
2
0
2
Order By: Relevance
“…The prevalence of IAC found in the present study was similar to that reported in the literature ( 7 - 8 , 24 ) . In the presence of the IAC diagnosis, the nurse must act in order to remove or minimize obstructions to facilitate the passage of air and promote gas exchange ( 25 ) .…”
Section: Discussionsupporting
confidence: 92%
“…The prevalence of IAC found in the present study was similar to that reported in the literature ( 7 - 8 , 24 ) . In the presence of the IAC diagnosis, the nurse must act in order to remove or minimize obstructions to facilitate the passage of air and promote gas exchange ( 25 ) .…”
Section: Discussionsupporting
confidence: 92%
“…Dessa maneira o estudo seguiu a Teoria da Adaptação de Callista Roy, por se tratar de um olhar holístico que considera as particularidades da paciente, de modo a proporcionar uma adaptação à nova situação clínica que a mesma se encontra diante das limitações proporcionadas pelas comorbidades atuais, que quando se somam às pré-existentes promovem uma obrigatória mudança na rotina de vida (DANTAS et al, 2017).…”
Section: Diante Do Exposto O Cuidado Prestado a Pacientes Suspeitos D...unclassified
“…Autoria própria baseada nos Diagnósticos de enfermagem da NANDA-I (HERDMAN e KAMITSURU, 2018), na Classificação das Intervenções de Enfermagem (NIC) (BULECHEK, G. M.; BUTCHER, H. K.; DOCHTERMAN, J. M, 2010) e na Teoria da Adaptação de CallistaRoy (ROY, 2001).5. DISCUSSÃOO PE baseado na Teoria da Adaptação é constituído por fases: avaliação comportamental, de estímulos, elaboração dos diagnósticos de enfermagem, a partir de então há estipulação de ações e objetivos, para posteriormente ocorrer a implementação e avaliação(DANTAS et al, 2017).Dessa maneira, as etapas primordiais se baseiam na análise de reações comportamentais do indivíduo frente a estimuladores internos e externos. Tal fato corrobora para aprimoramento de intervenções e planejamento que contemple o ser humano abrangendo todos os seus âmbitos( SILVA et al, 2020).No estudo de caso apresentado a paciente desenvolveu novas patologias em decorrência da infecção por covid-19, apresentando problemas de enfermagem relacionados ao modo adaptativo fisiológico como: retenção de líquidos, fraqueza muscular, palidez e hipotensão.…”
unclassified
“…This can be contextualized through the Roy's adaptation model, where the subject is considered an adaptive and holistic being, visualized in the form of a system in which the inputs correspond to the stimuli and the outputs to the responses generated, which are control processes, such as coping or feedback mechanisms. 17,9 In response to criminality and negative events, control and prevention campaigns, programs and policies against drugs are implemented, and support and dialogue within families and the social circle of individuals are stimulated. There are challenges to develop strategies capable of dealing with and addressing drug dependence, and there is a need to increase evaluative research in this area.…”
Section: Description Of the Familymentioning
confidence: 99%
“…This is portrayed by Roy when he addresses the issue of role playing, representing the role of individuals in society from the perspective of their pattern of social interaction with others, whose perception is what leads towards a behavior resulting from regulatory mechanisms. 17 Patriarch's daughter 2: "It destroyed our family, in situations of chronic diseases, traumas, losses, ecological transitions and old age, where actions for violence prevention, strengthening of skills, greater feeling of belonging in the community, and quality of relationships prevail. This is accomplished by a set of effective strategies in the fight against moments of crisis for the reduction of pathological symptoms such as depression and vulnerability to risky situations.…”
Section: Drug Use Trafficking and Violence Issues Inmentioning
confidence: 99%